A study on the viability of minimum quantity lubrication with water in grinding of ceramics using a hybrid-bonded diamond wheel - Nascimento, Wesley Rodrigues do [UNESP]; Yamamoto, Adriano Akio [UNESP]; Mello, Hamilton José de [UNESP]; Canarim, Rubens Chinali [UNESP]; Aguiar, Paulo Roberto de [UNESP]; Bianchi, Eduardo Carlos [UNESP] (SAGE Publications, 2015)
With the currently strict environmental law in present days, researchers and industries are seeking to reduce the amount of cutting fluid used in machining. Minimum quantity lubrication is a potential alternative to reduce environmental impacts and overall process costs. This technique can substantially reduce cutting fluids in grinding, as well as provide better performance in relation to conventional cutting fluid application (abundant fluid flow). The present work aims to test the viability of minimum quantity lubrication (with and without water) in grinding of advanced ceramics, when compared to conventional method (abundant fluid flow). Measured output variables were grinding power, surface roughness, roundness errors and wheel wear, as well as scanning electron micrographs. The results show that minimum quantity lubrication with water (1:1) was superior to conventional lubrication-cooling in terms of surface quality, also reducing wheel wear, when compared to the other methods tested.
Keywords: Advanced ceramics; Grinding; Cutting fluids; Minimum quantity lubrication